Polygnathids (Conodonta) around the Pragian/Emsian boundary from the Dacun-1 section (central Guangxi, South China). (November 2019) - Lu, Jian-Feng; Valenzuela-Ríos, José Ignacio; Liao, Jau-Chyn; Wang, Yi
Abstract: The base of the Emsian, which is defined by the first appearance of the conodont Polygnathus kitabicus, has never been successfully demonstrated in the South China Block (including Guangxi and eastern Yunnan). As a result, we studied conodonts from the lowermost part of the Shizhou Member of the Yukiang Formation at the Dacun-1 section in the Liujing area, Guangxi. This new investigation has revealed a conodont fauna only consisting of Polygnathus pireneae, P . sokolovi, P . kitabicus, P . sp. and Pandorinellina exigua philipi, which can be assigned to the uppermost part of the pireneae Zone and the lowermost part of the kitabicus Zone in ascending order. The Pragian/Emsian boundary at the Dacun-1 section is located in the highest thick-bedded limestone bed that can be observed in the lowermost part of the Shizhou Member. Therefore, this is the first time that the lower boundary of the Emsian defined by the lowest occurrence of P . kitabicus is reported in the South China Block. However, the scarcity of suitable limestone samples for conodont analysis in the middle and upper parts of the Shizhou Member precludes definitive identification of the upper boundary of the kitabicus Zone in the Liujing area.